Four Lives, Two Cars, and a Colony. (23rd September 2021) - Lewis, Su Lin; Bickers, Robert
Abstract: Prompted by the closure of archives and new ways of working during lockdown, Su Lin Lewis and Robert Bickers find an unexpected intersection in their own family histories. Photographs of their grandparents were taken a decade and a hundred miles apart but betray parallel histories of migration, war, and social aspiration amid the decolonization of Malaya and the birth of a new Malaysia. The car is a symbol of social mobility both forwards and up, in a colony whose wealth of natural resources helped fuel the postwar explosion of the global middle class. This piece reminds us that even when we are confined to our homes, with albums as our archives, we can also find new possibilities in the banality of everyday social histories, perhaps richer when woven together.